The Cambridge companion to Greek and Roman philosophy - Sedley, D. N. (Cambridge University Press, 2003)
The Cambridge Companion to Greek and Roman Philosophy is a wide-ranging 2003 introduction to the study of philosophy in the ancient world. A team of leading specialists surveys the developments of the period and evaluates a comprehensive series of major thinkers, ranging from Pythagoras to Epicurus. There are also separate chapters on how philosophy in the ancient world interacted with religion, literature and science, and a final chapter traces the seminal influence of Greek and Roman philosophy down to the seventeenth century. Practical elements such as tables, illustrations, a glossary, and extensive advice on further reading make it an ideal book to accompany survey courses on the history of ancient philosophy. It will be an invaluable guide for all who are interested in the philosophical thought of this rich and formative period.